Prevalensi Tumor Payudara di RS Hermina Daan Mogot pada Tahun 2017-2021 - Febrina Githa Agatha; Shintia Christina; Purnamawati Purnamawati (Jurnal MedScientiae, 2023)
Breast cancer is the number one cause of death in developing countries. The purpose of this study was to determine the prevalence and characteristics of breast tumor patients based on histopathological examination at Hermina Daan Mogot Hospital in 2017-2021. This research is an observational descriptive cross-sectional technique regarding breast tumors with parameters such as age, clinical diagnosis and histopathological diagnosis.. In this study, 716 subjects met the inclusion and exclusion criteria. histopathological diagnosis with the most results of mammary carcinoma at the age of 40-49 (40.86%) and the most histopathological diagnosis of fibroadenoma mammary at the age of 20-29 (37.35%). The most common clinical diagnosis consistent with the histopathological diagnosis is fibroadenoma mammary, which is part of a fibroepithelial tumor. The least common clinical diagnosis was papilloma (0.4%) and the least clinical diagnosis was papillary lesion (0.3%), where the papilloma was part of the papillary lesion. Early breast examination is needed to be able to detect malignant lesions at an early stage so that appropriate management can be carried out immediately so as to increase the patient's life expectancy.